2016
DOI: 10.1002/ptr.5603
|View full text |Cite
|
Sign up to set email alerts
|

Slimming and Appetite-Suppressing Effects of Caraway Aqueous Extract as a Natural Therapy in Physically Active Women

Abstract: Following the current 'Globesity' trend, there is an increasing demand for alternative natural therapies for weight management. Numerous phytoconstituents reduce body weight through suppressing appetite and reducing food intake. Caraway (Carum carvi L.) is one of the medicinal plants that is traditionally used for weight loss. In this study, the appetite-suppressing effects of caraway aqueous extract (CAE) on 70 aerobically trained, overweight, and obese women were examined in a triple-blind, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…A delay in glucose absorption indeed indicates another mechanism than the α‐glucosidase inhibition previously reported for some herbs (Sivasothy et al ., ). If such SGLT‐1 inhibitions were confirmed by further studies, these natural products, as diet supplements, could also be interesting anti‐obesity factors (Yang et al ., ; Kazemipoor et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A delay in glucose absorption indeed indicates another mechanism than the α‐glucosidase inhibition previously reported for some herbs (Sivasothy et al ., ). If such SGLT‐1 inhibitions were confirmed by further studies, these natural products, as diet supplements, could also be interesting anti‐obesity factors (Yang et al ., ; Kazemipoor et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Persicum have antidiabetic and Appetite-Suppressing properties. The hypoglycemic, antihyperlipidemic and appetite reducing effects of caraway in humans and rats have been shown before (13,25) . Because bunium persicum is used widely in Iranian traditional medicine and as a common spice in Iranian foods, and to the best of our knowledge, there had been no clinical study on the effect of Bunium persicum on metabolic status of overweight and obese patients with type 2 diabetes and also, previous related studies have reported some inconsistent results; the present study was conducted to evaluate the effect of Bunium Persicum powder on glycemic indices, lipid profiles and serum levels of nesfatin-1 in overweight and obese patients with type 2 diabetes.…”
Section: Accordingly This Study Is Based On the Hypothesis That Bioamentioning
confidence: 68%
“…as regards, no article was found similar to our study, the sample size determined by considering the sample size of the similar studies in obese and overweight patients (31,32) and using the extract of anti-obesity factors (25) , The sample size determined from 8 to 44 in each group. The sample size for this study according to study limitations (control of various factors such as powder consumption, diet control, physical activity, nutritional counseling, cost) in each group 27 patients are considered but accounting to 10% missing during the study, the number of patients is 30 in each group.…”
Section: Homa-ir = Fbi [µIu/ml] × Fbs [Mg/dl] / 405mentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, evidence has suggested that Bunium Persicum and Carum Carvi are plant members of the Apiaceae family and have similar active ingredients (33,34) . In addition, slimming, appetite-suppressing, hypoglycemic, and antihyperlipidemic effects of Carum Carvi have been shown in recent studies (35,36) .…”
Section: Introductionmentioning
confidence: 93%